Effect Of N, P and K Fertilizers on Growth Performance and Phosotynthetic Pigments of Bidens biternata (Lour.) Merr. & Sherff. - Aiilawat, A. S.; Dagar, J. C. (Indian Forester, 1980)
Nitrogen, phosphorus and potassium fertilizers individually as well as in different combination have great impact on growth and photosynthetic pigments of Bidens biternata (Lour.) Merr. & Sherff, a medicinal herb. Nitrogen plays a great role in various growth parameters and photosynthetic pigments specially when it was supplied in combinations with potassium, phosphorus or both. Potassium and phusporus when supplied individually or in combinations with one another, were found to retard dry matter production of roots and shoots, photosynthetic pigments, RGR, NAR, LAI along with flower and achene production.